Implementation of Circular Economy in Regional Public Service Agencies in Waste Management as a Waste Reduction Strategy in Indonesia - Putri Nurmalasari; Januar Eko Prasetio; Kusharyanti Kusharyanti (Journal of International Conference Proceedings, 2024)
This study explores the implementation of the circular economy in waste management at UPTD Pelayanan Persampahan Kota Cimahi, which operates as a Regional Public Service Agency (BLUD) and functions as a quasi-public entity. As a BLUD, UPTD has the flexibility to manage waste processes independently and efficiently, converting waste into Refuse Derived Fuel (RDF), which is then sold to PT Indocement as an alternative fuel in cement production. The research uses a qualitative case study approach, gathering data through in-depth interviews, observations, and documentation to examine the systematic stages of waste processing. Waste collected from various sources, such as offices, hospitals, markets, and residential areas, is processed into RDF. This circular economy cycle enables the cement produced with RDF to be reused by the community, including the original waste-generating consumers. Findings reveal that this model not only reduces environmental impact by diverting waste from landfills but also generates economic value, highlighting the potential for sustainable partnerships between public waste management and private industry. The study suggests that optimizing BLUD’s quasi-public entity status and applying a circular economy model could enhance the effectiveness of responsible, sustainable waste management practices.